2004
DOI: 10.1111/j.1439-0523.2004.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and potentials of a mutated dwarfing gene ndf1 in Brassica napus

Abstract: A dwarf mutant ÔNDF-1Õ, approximately 70 cm high, was derived from a 200-cm high doubled haploid (DH) line Ô3529Õ (Brassica napus), seeds of which were jointly treated with chemical inducers and bombardment of fast neutron. The leaves of the ÔNDF-1Õ mutant were wrinkled and thicker compared with the wild-type control. The mutant had much lower values than its original parents for all agronomic traits, except for its seed weight. A genetic analysis revealed that dwarfism is under the control of a major gene (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 7 publications
1
25
1
Order By: Relevance
“…As a result, it was expected that resistance to lodging in this cultivar will be significantly greater and it was confirmed in this study. Wang et al (2004) assumed that semi-dwarf hybrids may exhibit high resistance to lodging only at high nitrogen fertilization.…”
Section: Traitsmentioning
confidence: 99%
“…As a result, it was expected that resistance to lodging in this cultivar will be significantly greater and it was confirmed in this study. Wang et al (2004) assumed that semi-dwarf hybrids may exhibit high resistance to lodging only at high nitrogen fertilization.…”
Section: Traitsmentioning
confidence: 99%
“…Shorter genotypes are discussed to be more resistant to lodging. Wang et al (2004) argued that the differing branching structure of semi-dwarfs, with branches starting at lower stem sections, led to a more even weight distribution throughout the plant. In this study, lodging was not scored in all environments, but, as an example, semi-dwarfs at location Einbeck in 2012-2013 revealed a higher resistance to lodging compared with normal types at high N fertilization (data not shown).…”
Section: Effect Of N Supply On Seed Yield and Agronomic Parametersmentioning
confidence: 99%
“…Despite better lodging resistance and advantages in harvest ability of semi-dwarf hybrids, this growth type did not gain a high market share in France and Western Europe; however, it is recommended in Eastern European countries because of improved winter hardiness (Pinochet and Renard, 2012). Wang et al (2004) described yet another dwarf mutation, ndf-1, as single gene with a mainly additive effect, which is described as allelic to bzh. Li et al (2011) showed that ndf-1 was a gibberellin-insensitive dwarf type.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to producing specific proteins, plants respond to various stresses in a similar manner by producing heat shock proteins (HSPs), indicating a similarity in the plant's adaptive mechanisms (Timperio et al 2008). In this sense, the HSPs and other chaperones keep proteins and RNA in their correct conformation in order to mitigate extreme temperatures (Wang et al 2004). Some of these HSPs are related to flour quality (Wardlaw et al 2002).…”
Section: Discussionmentioning
confidence: 99%